2019
DOI: 10.1101/765768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How neurons move during action potentials

Abstract: Neurons undergo nanometer-scale deformations during action potentials, and the underlying mechanism has been actively debated for decades. Previous observations were limited to a single spot or the cell boundary, while movement across the entire neuron during the action potential remained unclear.We report full-field imaging of cellular deformations accompanying the action potential in mammalian neuron somas (-1.8nm~1.3nm) and neurites (-0.7nm~0.9nm), using fast quantitative phase imaging with a temporal resol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…Rapid cellular deformations accompanying the changes in the transmembrane potential have been observed in multiple cell types, including the recent full-field interferometric imaging of HEK cells and neurons in culture [7]- [10], [14]. These measurements have established a linear relationship in typical cells between the membrane displacement and changes in cell potential, linked by the dependence of the membrane tension on transmembrane voltage.…”
Section: Voltage-dependent Membrane Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid cellular deformations accompanying the changes in the transmembrane potential have been observed in multiple cell types, including the recent full-field interferometric imaging of HEK cells and neurons in culture [7]- [10], [14]. These measurements have established a linear relationship in typical cells between the membrane displacement and changes in cell potential, linked by the dependence of the membrane tension on transmembrane voltage.…”
Section: Voltage-dependent Membrane Tensionmentioning
confidence: 99%
“…To relate the observed mechanical deformations of cells to the underlying physiological processes, the coupling mechanisms must be known. Recently, we demonstrated that nm-scale deformations in neurons and other electrogenic cells can be explained by the voltage dependence of the membrane tension [8], [10]. Changes in the membrane tension necessarily cause a deformation to rebalance forces across the structure, whether it's a whole cell or an organelle.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative phase imaging has been used to analyze diverse processes (9), such as, membrane mechanics, density of organelles, cell migration and more recently propagation of action potential (29). Polarized light imaging has enabled discovery of the dynamic microtubule spindle (5), assessment of structural integrity of meiotic spindles of oocytes in invitro fertilization (IVF) clinics (30), label-free imaging of white matter in adult human brain tissue slices (28,31), and imaging of activity-dependent structural changes in brain tissue (32).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the physiological processes associated with neural activity affect the cell's refractive index 4 and shape [5][6][7] , which together alter the light propagation, including changes in light scattering 8,9 , polarization 10 and optical path length (OPL) 5 . Similarly, cellular deformations accompanying the trans-membrane voltage change during the action potential have been documented in crustacean nerves 11,12 , squid giant axons 13 and mammalian neurons 7,14,15 . Interferometric imaging of such changes in general, and cellular deformations associated with variations in the cell potential, in particular, offers a non-invasive label-free optical approach to monitor the electrical activity in neurons 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Using atomic force microscopy, Zhang et al demonstrated that HEK293 cells deformed proportionally to the membrane potential change (1 nm per 100 mV) 19 . Using quantitative phase microscopy, Ling et al demonstrated cellular deformations of up to 3 nm during the action potential in spiking HEK293 cells 6 , and about 1 nm in mammalian neurons 7 . Detecting the ms-fast and nm-scale cellular deformations in transmission is very challenging since the OPL difference between the cells and the surrounding medium scales with the refractive index difference, which is only ≈ 0.02.…”
Section: Introductionmentioning
confidence: 99%